2020
DOI: 10.1088/1572-9494/ab6906
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear properties of Z = 114 isotopes and shell structure of 298114

Abstract: The two-neutron separation energies (S2n) and α-decay energies (Qα) of the Z = 114 isotopes are calculated by the deformed Skyrme–Hartree–Fock–Bogoliubov (SHFB) approach with the SLy5, T22, T32 and T43 interactions. It is found that the tensor force effect on the bulk properties is weak and the shell closure at N  = 184 is seen evidently with these interactions by analyzing the S2n and Qα evolutions with neutron number N . Meanwhile, the single-particle energy spectra of 298114 are studied using the spherical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…( 2) and the l values are shown in columns 3 and 4 of Table 2, respectively. Note that the l values are determined by the spinparity selection rule, and the spin and parity values of the initial and final states are taken from the NUBASE2020 table [95]. The predicted radioactive half-lives within the UFM are shown in column 5 of Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 2) and the l values are shown in columns 3 and 4 of Table 2, respectively. Note that the l values are determined by the spinparity selection rule, and the spin and parity values of the initial and final states are taken from the NUBASE2020 table [95]. The predicted radioactive half-lives within the UFM are shown in column 5 of Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, these models share the same mechanism which leads to similar half-lives. Since the mechanism of radioactivity is similar to that of -decay [96][97][98][99][100], the cluster-like or fission-like models that can describe -decay can reproduce the experimental half-lives of radioactivity. Recently, an extended constraint criterion on the half-life, -12< <2 s, was proposed to identify the most probable decay candidates [89] for future 2p experiments, based on the work of Olsen et al [62].…”
Section: Resultsmentioning
confidence: 99%
“…( 16). Regarding the unknown nuclear masses, their values were calculated from the empirical masses of the NU-BASE2016 table [56] or the WS4 mass table [85] be- cause relevant studies showed that the WS4 mass model can predict the experimental nuclear masses and decay energies accurately [85][86][87][88]. We hope these predicted half-lives will be useful for identifying new cluster emissions of the trans-tin region in future measurements.…”
Section: Resultsmentioning
confidence: 99%
“…With the construction of a new generation of radioactive beam facilities and the development of the new detection technology, study on the exotic decay properties of unstable nuclei has been a hot subject in nuclear physics [1][2][3][4][5][6][7][8][9]. Nowadays, the proton radioactivity has been recognized as one of the exotic decay modes and paid attention by many researchers [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%